Compression analysis of external double-layered flange connection in transmission tower. (October 2021) - Li, Chao; Deng, Hong-Zhou; Gao, Yi-Ran; Song, Xue-Qi; Hu, Xiao-Yi
Abstract: In this study, an experiment was conducted to investigate the bearing behaviour of an external double-layered (EDL) flange connection under axial compression. The initial geometric imperfection of the flange plates was measured before the experiment to evaluate its effect on the compression capacity. Furthermore, finite element analysis was conducted and its results were compared with the experimental results. The initial imperfection was observed to be strongly related to the mechanical properties of the EDL flange connection. Moreover, stresses at symmetrical positions of the end plates and stiffened plates were asymmetrical, and most of the stiffened plates fully yielded in their sections adjacent to the end plates. On the basis of the initial imperfection measurements, three basic imperfection modes were proposed for the end plate. Finite element models considering these modes could predict the experimental results well. The load distribution coefficients of a stiffened plate and an end plate were obtained by considering the initial imperfection, and they are presented here along with practical design methods for the two components.